2011
DOI: 10.1007/s10963-011-9045-7
|View full text |Cite
|
Sign up to set email alerts
|

The Secondary Products Revolution: Empirical Evidence and its Current Zooarchaeological Critique

Abstract: Andrew Sherratt is perhaps best known for the concept of a 'Secondary Products Revolution', which stressed that the 'primary' pattern of exploiting domesticated animals for meat in the Early Neolithic was followed by a more diversified exploitation of secondary applications and products such as milk, wool, textiles, and traction. This paper discusses how changes in animal exploitation in the European Neolithic, including secondary uses and products, can be inferred from faunal remains. It also challenges a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 14 publications
2
23
0
2
Order By: Relevance
“…Similar mortality profiles elsewhere have been taken to indicate dairy husbandry (e.g. Iceland, Hambrecht, 2009; see also Marciniak, 2011). However an alternative explanation for a high level of infant calf mortality has been suggested (McCormick, 1998).…”
Section: Cladh Hallansupporting
confidence: 53%
“…Similar mortality profiles elsewhere have been taken to indicate dairy husbandry (e.g. Iceland, Hambrecht, 2009; see also Marciniak, 2011). However an alternative explanation for a high level of infant calf mortality has been suggested (McCormick, 1998).…”
Section: Cladh Hallansupporting
confidence: 53%
“…A large number of animal by-products such as leather, bones, blood, and feathers, among others, were used as raw materials to manufacture artifacts that fulfill a variety of functions, such as clothing, personal ornamentation, tools, and dwellings. These by-products were also consumed for ritual purposes (Fiore, 2011;Goepfert, 2010;Marciniak, 1999Marciniak, , 2011Ratto and Basile, 2013;Russell, 2012;Szpak et al, 2014). Furthermore, the ways peoples value, use and relate to animals have been mediated by particular cosmologies (Descola, 1996(Descola, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…7 The delay between the focus on primary and then on secondary products is however in the academic literature a matter of debate and controversy (Helmer and Vigne 2007;Marciniak, 2011).…”
Section: From Management To Tamingmentioning
confidence: 99%
“…First it has been demonstrated that the strict association of the SPR with the late Neolithic phase was a strong assumption. Indeed, the changes that might be linked with the Secondary Products Revolution are by no means associated with a single century or millennium and emerged in different periods across the Near-East (Marciniak, 2011). Second, by interpreting slaughtering age profiles which reflect animal management strategies, Helmer and Vigne (2007) provide clear evidence for milk exploitation of sheep and goats as early as the first advances of the Neolithic in the Near East.…”
Section: Milk Exploitationmentioning
confidence: 99%